LEGAL ISSUES OF STATE DUTY REFUND UNDER THE LEGISLATION OF UZBEKISTAN - Ibratova Feruza Babakulovna (Journals Park Publishing, 2025)
The article examines the grounds and procedure for the return of state duty under the legislation of Uzbekistan. This legal mechanism ensures the protection of the property interests of persons participating in economic disputes, if there are legal grounds for the return of the amount paid.
Keywords: Return of state duty, economic process, legal costs, grounds for return.